Representação e ciências sociais - Silva, Drance Elias da (Revista Ágora Filosófica, 2016)
This Article may be situated within the rapport field between Philosophy and Social Sciences, at the search regarding to the concept concerning the Representation. Regarding to Philosophy, under a general view, the concept, concerning Representation, has been, since a long time, understood as a trail which one would get througl reaching to the real and true ones. Representation, as the thought contents expression form had not been known departing from Philosophy as a barrier against the objectivity concerning the knowledge. Representation, in its source, has been constituting itself a cognictive, inmanent reflection, related to the conscience inner subjectivity. But departing from the episthemological point of view, it has been not so easy for the campus concerning the Culture Sciences as a totality. In the theory regarding to knowledge, the Social Sciences campus and, more specifically, in the human life Symbolic dimension constitutive aspects, it has been, often, accepted negatively as an entry door for the histotical social reality. Nowadays, one may conclude that the contents concerning the Culture are deeply rooted within the histotical reality, which may present new dimension the reading regarding to the Symbolical side concerning the human life, under the view regarding to the unseen aspect, such as the intellectualistic Western dominant Culture allows understanding the way which could be in.